Simultaneous selection of the appropriate technology and its optimal technology transfer method from the preferred supplier applying BWM and grey ANP methods - Ali Bonyadi Naieni; Sirous Amirghodsi; Ahmad Makui (Muṭāli̒āt-i Mudīriyyat-i Ṣan̒atī, 2020)
One of the important decisions in the supply chain is the supplier selection affecting different sectors and objectives of a chain significantly. When it comes to supplier selection, product/technology selection, product/technology transfer method selection, and product/technology supplier selection are three debatable factors. Hence, in this paper, criteria influencing these three indicators will be identified and their importance will be ranked by Gray-DEMETEL and Best-Worst Method (BWM). Then, the priority of the options will be determined using Gray Analytical Network Process (GANP), which is one of the strongest decision-making methods. This paper attempts to demonstrate the superiority of the BWM method in determining the importance of criteria while comparing to previous methods in this group. The compliance rate obtained for the BWM confirms this claim. In order to investigate the proposed approach, a case study was conducted while considering 5 final suppliers, 3 technologies and 5 technology transfer methods, which ended with the selection of the best supplier with the highest technology and capable of transferring the technology by the optimal transfer method.